Self-assembly in tailor-made polyfluorenes: synergistic effect of porous spherical morphology and fret for visual sensing of bilirubin - Senthilkumar, T.; Asha, S. K. (Macromolecules, 2013)
Two new fluorene-based homo- (PDP-PF) and copolymers (PDPPF-co-Ph) were synthesized with a bulky 3-pentadecylphenoxy (PDP) group appended hexyl chains at the 9, 9' position using Suzuki coupling polymerization. Investigation on the morphology of the polymers using microscopic techniques like TEM and AFM indicated formation of self-assembled nanostructures like vesicles by PDP-PF and porous spheres by PDPPF-co-Ph respectively. Dynamic as well as static light scattering studies (DLS, SLS) in THF also indicated the existence of self-assembled nanosized particles in solution with a shape factor (rho) of 0.76 and 0.96 for PDP-PF and PDPPF-co-Ph, respectively, confirming the existence of vesicles in the case of the former and spherical particles in the case of the latter polymer. The favorable photophysical properties of the polyfluorenes were taken advantage of for the selective sensing of unbound bilirubin (BR) in THF. A high energy transfer efficiency of 86% upon addition of bilirubin with color change from blue (polyfluorene emission) to green (FRET-induced bilirubin emission) was observed with PDPPF-co-Ph. Steady state fluorescence measurements gave a minimum donor-acceptor distance of 36 A(0) and time-resolved fluorescence decay measurements showed a reduction in average lifetime of PDPPF-co-Ph (from 450 to 240 ps) upon addition of bilirubin indicating efficient energy transfer. The open porous spherical assembly of PDPPF-co-Ph enabled better adsorption of the analyte, which along with the good spectral overlap resulted in greater efficiency for FRET-induced energy transfer. Sensing of unbound bilirubin was also attempted in THF/water solvent mixture in an effort to simulate the unbound (THF soluble) and bound (water-soluble) bilirubin equilibrium. Enhancement of bilirubin emission coupled with quenching of polyfluorene emission makes this approach adaptable for visual fluorimetric color change (blue to green) based sensor. Structural analogues such as biliverdin and porphyrin showed poor fluorescence quenching efficiency, thus highlighting the selectivity and sensitivity of the FRET-based sensing of bilirubin by the newly designed polyfluorene.

Easy `filter-and-separate' method for enantioselective separation and chiral sensing of substrates using a biomimetic homochiral polymer - Senthilkumar, T.; Asha, S. K. (Chemical Communications, 2015)
We present a polyfluorene appended with protected L-glutamic acid that exhibited a reversible alpha-helix/beta-sheet-like conformation and helical porous fibrous morphology mimicking the super-structure of proteins. The new homochiral polymer probe enabled efficient heterogeneous enantioselective separation and chiral sensing of a wide variety of substrates from their aqueous racemic mixture using an easy `Filter-and-Separate' method.

Selective and sensitive sensing of free bilirubin in human serum using water-soluble polyfluorene as fluorescent probe - Senthilkumar, T.; Asha, S. K. (Macromolecules, 2015)
The adherence of serum protein on conjugated polymer is a major bottleneck in the application of the latter for selective sensing of small biomolecules in blood serum. In this report, we present new polyfluorenes with d-glucuronic acid appendage that is a nonreceptor for any serum protein, thereby providing a platform for selective sensing of free bilirubin in the clinically relevant range of <25 to >50 mu mol/L in human blood serum. The appended d-glucuronic acid formed noncovalent interactions with bilirubin, which in conjunction with favorable spectral overlap between the polymers and bilirubin facilitated efficient FRET process in aqueous solutions. Addition of bilirubin resulted in the quenching of the polyfluorene emission with simultaneous appearance of bilirubin emission exhibiting visual emission color change from blue to light green. The polymer remained stable in serum even under severe basic conditions and exhibited high selectivity with visual sensitivity only toward free bilirubin in human serum in the presence of crucial interferences such as hemoglobin, proteins, biliverdin, glucose, cholesterol, and metal ions. Nanomolar sensing of bilirubin could also be demonstrated successfully using one of the d-glucuronic acid appended polymer (PF-Ph-GlcA), which could sense similar to 150 nm of bilirubin in human serum. The combined role of energy transfer and noncovalent interaction highlights the potential of the new polymer design for highly selective sensing activity in complex biofluids.

Orientation effect induced selective chelation of Fe2+ to a glutamic acid appended conjugated polymer for sensing and live cell imaging - Senthilkumar, T.; Parekh, Nimisha; Nikama, Shrikant B.; Asha, S. K. (Journal of Materials Chemistry B, 2016)
Intracellular detection and imaging of labile iron(II) pools is very important in tracking physiological processes that demand new and rapid sensing probes. In this report, we present a water soluble polymer based probe for the fluorescence sensing and live cell imaging of labile Fe2+ ions with high selectivity for the first time. The polymer probe was based on conjugated polyfluorene which was appended with amino acid (L-glutamic acid). The biocompatibility of the polymer was confirmed from an MTT assay which demonstrated >90% cell viability even at 300 mu g ml(-1) loading of polymers. Simple glutamic acid did not show selectivity towards any of the divalent ions. However, glutamic acid appended polyfluorene exhibited selective chelation to Fe2+ ions resulting in immediate sensing activity for Fe2+ ions in water and living cells with fluorescence turn-off response. The limit of detection of the PF-Ph-GA polymer probe was 46 (+/- 2) nM which indicated high sensitivity for Fe2+ over other ions reported in the literature. The polymer also exhibited improved sensing activity in the range of intracellular pH (5-9) which is advantageous in differentiating endogenous changes. The probe was successfully applied for the fluorescence imaging of intracellular and supplemented labile iron(II) pools in living HeLa cells.